Manufacturing technology for flexible thermoresistors on polyimide base - Dinev, D. A.; Zhora, V. D.; Grigoryeva, N. N.; Grunyanskaya, V. P. (Technology and design in electronic equipment, 2013)
The article proposes the manufacturing technology for flexible thermoresistors on polyimide film and analyzes their advantages in relation to other temperature sensors. Such heating elements provide good thermal contact with the controlled object of complex shape. In addition, they are quick-response, reliable and easy to manufacture.